Stability Analysis of Sampled-Data Systems Using Sum of Squares - Seuret, A.; Peet, M. M. (IEEE transactions on automatic control, 2013)
This technical brief proposes a new approach to stability analysis of linear systems with sampled-data inputs or channels. The method, based on a variation of the discrete-time Lyapunov approach, provides stability conditions using functional variables subject to convex constraints. These stability conditions can be solved using the sum of squares methodology with little or no conservatism in both the case of synchronous and asynchronous sampling. Numerical examples are included to show convergence.